Perioperative fluid balance in children undergoing open heart surgery - Mozol, Krzysztof; Haponiuk, Ireneusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Perioperative fluid balance is a leading problem in paediatric cardiac surgery. The multifactor phenomena lead to increase of fluid retention during and after surgical procedures. The reduction of surgical and technical trauma as well as specific haemofiltration techniques would improve results and reduce perioperative mortality and morbidity.